2022
DOI: 10.1186/s41687-022-00418-1
|View full text |Cite
|
Sign up to set email alerts
|

To share or not to share: communication of caregiver-reported outcomes when a patient has colorectal cancer

Abstract: Background The importance of patient-centered measurement in cancer care has led to recognition of the potential for caregiver-reported outcomes to improve caregiver, patient and healthcare system outcomes. Yet, there is limited evidence to inform caregiver-reported outcome implementation. Our purpose was to generate evidence to inform the meaningful and constructive integration of caregiver-reported outcomes into cancer care to benefit caregivers, including exploration of the question of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, family members were concerned that patients’ fears were not alleviated. There is a chance that this actually reflects poor communication between patients and their family members [ 32 ] – not telling relatives what they need [ 14 ]. It is also likely that family members themselves have their own fears about the patient’s illness and deterioration [ 33 ] and were reporting these fears rather than those of the patient [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, family members were concerned that patients’ fears were not alleviated. There is a chance that this actually reflects poor communication between patients and their family members [ 32 ] – not telling relatives what they need [ 14 ]. It is also likely that family members themselves have their own fears about the patient’s illness and deterioration [ 33 ] and were reporting these fears rather than those of the patient [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Howard et al (2022) and Siwik et al (2022) reported that patients with cancer are also prone to feelings of shame and guilt: some cancer patients believe that their illness is their punishment for their wrong deeds, and some others feel guilty about the burden and costs of their care imposed on their families. 35,36 Liberation from social isolation is another sub-theme under the theme of managing psychological tension in patients who attempted suicide. Overcoming their reluctance to communicate with other people can enable the patients to become aware of people's real feelings about themselves and their great joy about the fact that they are alive, which will help them abandon their unrealistic thoughts and preconceptions.…”
Section: Discussionmentioning
confidence: 99%
“…The protocol was approved by the harmonized BC Cancer and University of British Columbia Research Ethics Board. Further details of study methods have been published elsewhere [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%